2016
DOI: 10.3390/molecules21081024
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Essential Oil Yield, Composition, and Antioxidant Activity of Different Plant Organs from Blumea balsamifera (L.) DC. at Different Growth Times

Abstract: Blumea balsamifera, also named Ainaxiang, is widely used as an ancient medicinal herb in tropical and subtropical Asia. It is rich in essential oils. In this work the essential oils of B. balsamifera from different plant organs and in different months were extracted, and then analyzed by gas chromatography-mass spectrometry. The results showed that essential oil yield of young leaves was the highest (0.65 mL/100 g), followed by mature leaves (0.57 mL/100 g), and the oil yield was higher in October (0.47 mL/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 10 publications
4
33
0
2
Order By: Relevance
“…It indicated that the ACs of EOs from the leaves of B. balsamifera growing from October to December were at a high level. This observation is consistent with previous studies [13]. The joint interpretation of PCA of chemical components and AC tests presented that the AC of EO from B. balsamifera was highly correlated with the chemical composition of EO.…”
Section: Antioxidant Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…It indicated that the ACs of EOs from the leaves of B. balsamifera growing from October to December were at a high level. This observation is consistent with previous studies [13]. The joint interpretation of PCA of chemical components and AC tests presented that the AC of EO from B. balsamifera was highly correlated with the chemical composition of EO.…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…Besides, the crude extracts, flavonoids, sesquiterpenoids, and triterpenoids were extracted from the leaves of B. balsamifera [7][8][9][10][11][12]. B. balsamifera, also named Ainaxiang, harvested from Yunnan and Hainan Province, China, had been used to extracted EOs using hydrodistillation according to the method noted in Pharmacopoeia of the People's Republic of China, and the compositions and antioxidant activities of EOs of different plant organs from B. balsamifera at different growth times were analysed and evaluated [13]. As is well known, the same species of plants cultivated in different regions have great differences in chemical composition [14].…”
Section: Introductionmentioning
confidence: 99%
“…15) The essential oils of young leaves and shoots of Blumea balsamifera have been shown to have strong antioxidant activities, which are mainly imparted by dimethoxydruene, α-caryophyllene, and β-caryophyllene. 16) Sun et al have also found that the essential oil…”
Section: Discussionmentioning
confidence: 96%
“…What is more, a clinical study reported that polypodium leucotomos extract treatment is safe and effective for melasma patients (Goh et al, 2018). As we all know, growing conditions (soil, water, climate), growth time, and harvest time have great impacts on herbs in cultivation (Yuan et al, 2016;Olennikov et al, 2017;Zhang et al, 2017). These factors will subsequently influence the components of herbal extracts, so do their effects (Bent and Ko, 2004).…”
Section: Herbal Extractsmentioning
confidence: 99%